Comportamiento de las exportaciones de bienes de la región Loreto, periodo 2014 - 2018 - Arimuya Macahuachi, Liz Karen (2021)
The research work Behavior of exports of goods from the Loreto region aims to analyze the behavior of exports from the Loreto region period 2014 - 2018, the research is descriptive level and of longitudinal non-experimental design, the sample is made up of all records on traditional and non-traditional exports in all economic activities that exist in SUNATADUANAS. Ten were the main destination countries, of which seven only made one purchase in the entire period: Argentina in 2016, Belgium in 2014, Chile in 2018, China in 2017, South Korea in the year 2018, Hong Kong in 2016, Panama in 2014; Colombia and the United States bought consecutively from 2015 to 2018, but Mexico was the only country that made purchases every year during the analysis period. Exports in general terms did not have a constant growth behavior, in the period there has been falls and rises in the amount. Non-traditional exports for three consecutive years (2015, 2016 and 2017) have amounts higher than traditional exports.